PENGARUH UKURAN, PERTUMBUHAN, DAN NILAI PERUSAHAAN TERHADAP TINDAKAN PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR - Rahmawati Rahmawati; Riyanto Wujarso (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
The purpose of this study is to examine the effect of firm size, growth, and price to book value of income smoothing. Firm size is measured by the natural logarithm of total assets. Growth is measured by the ratio of sales in year t after deducting sales in the previous period to sales in the previous period. Price to Book Value is measured by the ratio of share price to book value of common stock. Income smoothing is measured using the eckel index. The results of the study showed that partially firm size has significant influence on income smoothing practices. Growth has significant on the practice of income smoothing. And price to book value has not significant to the income smoothing practices. Simultaneously, company size, growth and value have a significant effect of 0.000. Nagelker's R square value is 0.313; it means that the coefficient of determination is 0.313. This states that the independent variable explains the variation of the dependent variable by 31.3% while the remaining 68.7% is influenced by other factors that are not examined.